On the Convergence of Nonconforming Finite Element Methods for the 2nd Order Elliptic Problem with the Lowest Regularity (Journal of Computational Mathematics, 2021)
The convergences ununiformly and uniformly are established for the nonconforming finite element methods for the second order elliptic problem with the lowest regularity, i.e., in the case that the solution $u \in H^1_0(Ω)$ only.
Keywords: Nonconforming finite element methods; Lowest regularity.